Ten-year-old Omani Girl with Lyme Arthritis - Tahani Al Mughaizwi; Hatem Al Rawahi; Nagi Elamin; Zaid Al Hinai; Zakariya Al Muharrmi; Laila S. Al Yazidi (Oman Medical Journal, 2022)
We report a 10-year-old girl who presented with acute arthritis of the left knee, which was confirmed as Lyme arthritis by serology and molecular assay. Careful history and examination were the keys to suspecting the diagnosis. The patient lived in the US for five years and her symptoms developed about a year after her return to Oman. To the best of our knowledge, this is the first case report of Lyme arthritis in Oman and the Arabian Gulf region. This case indicates the need to suspect Lyme disease in patients presenting with compatible symptoms and a history of recent travel to endemic regions.